Multimerization of anti‐(epidermal growth factor receptor) IgG fragments induces an antitumor effect: the case for humanized 528 scFv multimers. (20th August 2013) - Asano, Ryutaro; Hagiwara, Yasuyo; Koyama, Noriaki; Masakari, Yosuke; Orimo, Ryota; Arai, Kyoko; Ogata, Hiromi; Furumoto, Shozo; Umetsu, Mitsuo; Kumagai, Izumi
<x xml:space="preserve">Abstract</x> The construction of antibody fragments has the potential to reduce the high cost of therapeutic antibody production, but the structures of these fragments, with monovalency and the lack of an Fc region, can lead to reduced function. Multimerization is one strategy for recovering function that also yields better tumor‐to‐blood ratios than IgGs or monomeric antibody fragments because of rapid tumor uptake and clearance. Here, we constructed single‐chain variable fragment (scFv) multimers by modifying the linker length and domain order of humanized anti‐(epidermal growth factor receptor) IgG 528 (h528) and tested their ability to inhibit tumor growth. h528 scFv multimers, expressed using a bacterial expression system, were successfully fractionated and inhibited cancer growth in a multimerization‐dependent manner, whereas the h528 scFv monomer showed no inhibition. h528 scFv trimers with variable heavy–light domain order and no linkers showed the highest in vitro and in vivo antitumor effects, which were comparable with those of the approved anti‐(epidermal growth factor receptor) therapeutic IgG Cetuximab and Panitumumab. The trimers were also structurally stable in vitro and in vivo, which may be attributable to a strong interaction between the variable heavy and variable light domains of h528 Fv. Thus, h528 scFv multimers, especially trimers, are attractive as the next generation of anti‐(epidermal growth factor receptor) therapeutic IgG and offer the possibility of low‐cost production.